Machado de Assis, this monstrous writer (between aberrations and spectacles) - Granja, Lucia [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2017)
Shortly before setting out to write Memorias Postumas de Bras Cubas (Epitaph of a small winner), Brazilian writer Machado de Assis was busy with the series of columns Notas Semanais, published in the newspaper O Cruzeiro, between June and September, 1878. For fourteen Sundays he commented on the exhibition of an eight-legged horse, a fishman, an armless dwarf and the euphoria for bullfighting in Rio de Janeiro. Broadly speaking, he was interested in what he saw as the degradation of cultural interests manifested in the taste of both readers and audience. Taking his questions to the paroxysm in the in the realm of literary experimentation, this monstrous writer, inclined to literary disproportions, used to his advantage all the possibilities that the writing of serials offered to him, as well as the plethora of forms admitted by that genre.
Keywords: Grotesque; Machado de Assis; Memorias Postumas de Bras Cubas (Epitaph of a small winner); Philosopher or dog? Quincas Borba; Serial Columns; Short stories